Mapa geozagrożeń gminy Sławków - Gołąb, Kamil (My University, 2013)
In the area of commune Sławków there are places threatened by mass movements, floods and inundation. Geohazards affect the existing and emerging infrastructure. Geomorphology, geology, tectonics and hydrology of commune were described. In order to create a map of geohazards ArcGis software was used. The map is based on existing studies and field data. The effect of studies constitutes the map showing the location of geohazards on the background of the existing infrastructure.

Na terenie gminy Sławków występują obszary zagrożone ruchami masowymi, powodziami oraz podtopieniami. Geozagrożenia wpływają na istniejącą i powstającą infrastrukturę. Opisano geomorfologię, geologię, tektonikę i hydrologię gminy. W celu stworzenia mapy geozagrożeń użyto oprogramowania ArcGis. Do tego wykorzystano istniejące opracowania oraz dane terenowe. Efektem jest mapa przedstawiająca lokalizację geozagrożeń na tle istniejącej infrastruktury.
Map of geohazards for commune Sławków
mapa (pdf).
Keywords: gmina Sławków; geozagrożenia; ruchy masowe; powodzie; mapa; commune Sławków; geohazards; mass movement; floods; map